Source Type Recognition Algorithm of Radio Emission using Radial Basis Functions - V. F. Korotkov; R. S. Zyryanov (Известия высших учебных заведений России: Радиоэлектроника)
This paper deals with the radio source type detection algorithm with a complicated time-frequency structure. The algorithm is based on splitting training data classes into sub-classes, and using them for making a decision about the type of radio source. Result of testing on simulated data is presented.